Minimal length curves in unitary orbits of a Hermitian compact operator - Bottazzi, Tamara Paula (2016)
Fil: Bottazzi, Tamara P. Instituto Argentino de Matemática “Alberto P. Calderón”. Buenos Aires, Argentina.